Experimental light-microscopic study of pathological dentinogenesis - Stevanović Radoje; Vojinović Jovan (Stomatološki glasnik Srbije, 2005)
The aim of this paper was to analyze pathological dentinogenesis in initial and subsequent developmental stages in relation to the type and intensity of irritations, by means of light microscopy. Material and method: Total of 70 teeth (16 human and 54 dog teeth). Cavity preparation was identical in all teeth, with the depth varying between 1-1.5mm in primary and 2-2.5mm in permanent teeth, respectively. Cavities were filled with calcium-hydroxide paste and were subsequently closed with amalgam restoration. Observational period ranged from 1 to 6 weeks. Results: Obtained results have shown that structure of the pathologically developed dentine depends on intensity more when compared to the type of irritation. Damaged regular odontoblasts, which are excreting tubular dentine (more irregular with more severe cell damage), act as formative cells. When regular odontoblasts are destroyed, new can be differentiated from precursors that are latent in the pulp and periodontal tissue. Conclusion: Formation of pathological dentine is of the regular dentinogenesis pattern. Pathological dentinogenesis in the process of odontoblast discharge has inverse course: it is more irregular with increased degradation. Pathological dentinogenesis is genetically conditioned process, which involves entire pulp-dentinal complex. .